EFEKTIVITAS PENERAPAN METODE DISKUSI DENGAN PENDEKATAN MATEMATIKA REALISTIK (PMR) DAN PENDEKATAN QUANTUM LEARNING (QL) DITINJAU DARI TIPE KEPRIBADIAN SISWA UNTUK MENINGKATKAN PRESTASI BELAJAR MATEMATIKA SISWA KELAS VIII SMP NEGERI DI KABUPATEN LAMPUNG TIM - Desty Septianawati (Jurnal Pembelajaran Matematika, 2013)
Abstract: The aims of this research are to know: (1) Which one more effective, learning using discussion with realistic mathematics approach, Quantum Learning (QL) or a conventional learning. (2) Which one gives better mathematics learning achievement, student with personality types Sanguine, Melancholy, Choleric or Phlegmatis. (3) Which one more effective for each personality type of students, learning using discussion with PMR, QL or a conventional learning. This research used quasi experimental method with its population included all of students of state junior high school in East Lampung Regency. Sampling was done by stratified cluster random sampling. The size of the samples was 303 students. The data collection technique were the document that was the last of examination the seven grade for initial capability data before the experiment, achievement tests for mathematics student achievement data, and questioner of personality types. The data was analyzed using analysis of variance. The conclusions of the research were as follows: (1) learning mathematics using discussion with PMR is as effective as learning mathematics using the method of discussion with QL. However, learning of mathematics using discussion with PMR approach is more effective than learning mathematics using discussion with conventional approach. Likewise, learning mathematics using discussion with QL approach is more effective than learning mathematics using discussion with conventional approach. (2) Students with personality types of Sanguine, Melancholy, Choleric, nor Phlegmatis have the same mathematics achievement. (3) For each personality type of students, learning using discussion with PMR approach is as effective as using discussion with QL. However, using discussion with PMR and QL approach is more effective than learning mathematics the method of discussion with conventional approach.Keywords: Realistic Mathematics Approach, Quantum Learning Approach, Personality Types